Curative effect of transcatheter arterial chemoembolization combined with radiofrequency ablation in treating hepatic cell carcinoma and the effect on serum markers - Fu-Qiang Jiang (Journal of Hainan Medical University, 2016)
Objective: To analyze the curative effect of transcatheter arterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) in treating hepatic cell carcinoma (HCC) and the effect on serum markers. Methods: A total of 106 cases of patients with hepatic cell carcinoma treated in our hospital were randomly divided into observation group (53 cases) who received transcatheter arterial chemoembolization combined with radiofrequency ablation therapy and control group (53 cases) who received transcatheter arterial chemoembolization therapy, and then differences in overall effect, indicators of inflammation and oxidative stress, tumor activity-related indicators and tumor recurrence-related indicators between two groups were compared. Results: 1 week and 2 weeks after treatment, the number of cases of CR and PR of observation group was higher than that of control group, the number of cases of SD was not different from that of control group, and the number of cases of PD was lower than that of control group; 2 weeks after treatment, serum MDA, SOD, GSH, CRP, TNF-α and ESR of two groups were without differences, and serum EC, VEGF, MMP, AFP, CA199 and GGT contents of observation group were significantly lower than those of control group. Conclusion: Transcatheter arterial chemoembolization combined with radiofrequency ablation therapy can effectively control the growth of liver cancer lesions, reduce the levels of tumorrelated serum markers and inhibit the activity of tumor cells.